ROLE OF IRRIGATION AND FERTILIZERS ON FLEA BEETLE, PHYLLOTRETA CRUCIFERAE GECZE. INFESTATION ON MUSTARD - CHOWDHURY, MANIDIPA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2009)
The experiments were conducted in the Instructional farm of Uttar BangaKrishiViswavidyalaya, Pundibari, Cooch Behar, West Bengal in two successive Rabi seasons of 2005-06 and 2006-07 to study the role of irrigation and fertilizers on flea beetle, Phyllotreta crucferaeGecze. infestation on mustard of a cultivar, namely NC-I (Jhumka) of Brassica campestris var. yellow sarson. Highest flea beetle population (2.15 at seedling and 3.04 at siliqua stage) were recorded on the crop grown without irrigation coupled with highest level of fertilizers (80:40:40 kg NPK/ha) while lowest level (1.07 and 1.68 at seedling and siliqua stage, respectively) were observed at highest level of irrigation (three) coupled with lowest level of fertilizers (40:20:20 kg NPK/ha).